THE EFFECT OF DEBT AND DIVIDEND POLICIES ON COMPANY VALUE IN PT UNILEVER INDONESIA Tbk LISTED ON THE NDONESIA STOCK EXCHANGE FOR THE PERIOD 2014-2023 - Lisdawati, Lisdawati; Rahmasari, Novia (Yayasan Education and Social Center, 2025)
This study aims to determine the effect of Debt-to-Equity Ratio and Dividend Payout Ratio on Firm Value (Earnings Per Share) at PT Unilever Indonesia Tbk, listed on the Indonesia Stock Exchange, for the 2014-2023 period. The research method used is an associative method with a quantitative approach. The data analysis used is descriptive statistical test, classical assumption test, regression analysis, coefficient of determination, T test, and F test. Based on the partial test results, the Debt Policy (Debt to Equity Ratio) has a significant negative effect on Company Value (Earnings Per Share) where the calculated T is -4.001 > T table 2.3646 with a significance value of 0.005 < 0.05 and partially the Dividend Policy (Dividend payout Ratio) does not have a significant positive effect on Company Value (Earnings Per Share) where the calculated t is 0.312 < t table 2.364 with a significance value of 0.764 > 0.05. Meanwhile, simultaneously, Debt Policy (Debt to Equity Ratio) and Dividend Policy (Dividend Payout Ratio) significantly influence Firm Value (Earnings Per Share), with the calculated F-value of 10.280 > F-table 4.74, with a significance value of 0.008 < 0.05. Furthermore, the Adjusted R-square value of 0.673 was obtained, indicating that the Debt Policy (Debt to Equity Ratio) and Dividend Policy (Dividend Payout Ratio) variables were able to explain 67.3% of Firm Value (Earnings Per Share), while the remaining 32.7% was influenced by other factors not examined in the study.